Pengaruh Komitmen Organisasi, Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Jamkrida Propinsi Kalimantan Selatan - Muhammad Saufi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to analyze the influence of Organizational Commitment, Organizational Culture and Work Motivation on Employee Performance of PT Jamkrida Kalsel. Sampling using saturated sampling method. Sampling based on predetermined criteria obtained a total sample of 41 respondents. The data analysis technique used Multiple Linear Regression analysis with the help of the SPSS computer program version 25. The results of this study indicate that Organizational Commitment, Organizational Culture and Work Motivation simultaneously have a significant effect on the Employee Performance of PT Jamkrida Kalsel. Organizational commitment has a significant positive effect on employee performance, organizational culture has a significant positive effect on employee performance and work motivation has a significant positive effect on employee performance of PT Jamkrida Kalsel. Organizational Commitment has the dominant effect on employee performance at PT Jamkrida Kalsel.